COMPULSIVE BUYING FOR STUDENTS MAKING ACCOUNTING UNIVERSITY IN BALI - Permata Dewi, I Gusti Ayu Ratih (International Journal of Social Science, 2023)
This study aims to analyze the factors that influence financial management behavior, namely financial literacy, financial attitude, financial education in the family, pocket money and financial self-efficacy and their impact on compulsive buying. The population of this study was 10,769 students of accounting study programs at universities in Bali. Sampling was determined using the slovin formula so that a total sample of 100 students. Data collection was carried out by distributing questionnaires via the Google form. The data analysis technique used is Smart-PLS. The results show that financial literacy, financial attitudes, and financial self-efficacy have a positive and significant effect on financial management behavior. Furthermore financial literacy, financial education in the family, and pocket money has an effect on financial self-efficacy. And finally, financial management behavior has a positive and significant effect on compulsive buying.